Vimentin Intermediate Filaments Maintain Membrane Potential of Mitochondria in Growing Neurites - Alexander A. Dayal; Olga I. Parfenteva; Huiying Wang; Blen Amare Gebreselase; Fatima K. Gyoeva; Irina B. Alieva; Alexander A. Minin (Biology)
Neural precursor cells contain two types of intermediate filaments (IFs): neurofilaments consisting of three IV type proteins and vimentin belonging to the type III IF proteins that disappear at the later stages of differentiation. The involvement of vimentin in neurogenesis was demonstrated earlier; however, the role of its temporary expression in neurons is not clear. We showed that the vimentin IFs that interacted with mitochondria maintained their membrane potential at the appropriate level, and thus, ensured their proper function. We examined the dependence of the mitochondrial membrane potential on the expression of vimentin in a CAD catecholaminergic neuronal cell line that was actively dividing in full culture media but stopped growing and started developing neurites when the serum was removed. Using the CRISPR Cas9 system to knock out the vimentin gene in these cells, we investigated the impact of this on the mitochondrial membrane potential. Our data show that the deletion of the vimentin IFs led to a decrease in the level of the mitochondrial potential. When the vimentin network in these cells was reconstituted by transfection with a plasmid that encoded human protein, the level of the potential was restored. Interestingly, mutated vimentin with a disrupted mitochondria-binding site had no such effect. Our data point to vimentin as a possible target in some neurological pathologies.